(untitled) (Third Sector Social Economic Review, 2018)
Today in the modern state, organisations that constitute the political structure of the society and the official mechanism that designate relationships between rulers and the ruled should be supported by some private organisations as well. In this scope, pressure groups, which emerged after industrial revolution in West, started to begin to develop only in multi-party periods and started to become partly diversified after 80s in Turkey. Businessman associations especially those founded in 70s and voluntary membership-based ones, notably TÜSİAD, chose to take on a social role instead of achieving short-term financial interest: In the process beginning in 1995 that takes Turkey to EU membership, by contacting related organisations both in the country and abroad, TÜSİAD started to reflect business world’s opinions and suggestions, and since that day it has been in all kinds of communication, representation, coordination and information practices in order to inform the public about these activitie: In this study, accepted as a pressure group, TÜSİAD’s view on EU about Turkey’s EU membership that comes down from past to present is studied through press release: As a result of the analysis that involves 2002-2007 period, it is concluded that TÜSİAD openly displayed its pressure group function through EU membership and hasn’t changed its EU discourse from past to present.